KAJIAN EKOWISATA BERBASIS KESESUAIAN KAWASAN DI PANTAI PULAU POMBO KABUPATEN MALUKU TENGAH - Maya M. S Puttileihalat; Henderina Lelloltery; Andry Tuhumury (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to known the suitability of the coastal area for beach ecotourism activities on Pombo Island. The research method used is a survey method with a qualitative descriptive approach. The sampling technique in this study was purposive sampling, which was divided into two observation stations by observing and interviewing the community. Observations were made on the characteristic conditions of the beach using several parameters related to the suitability of beach tourism. The analytical method used is the analysis of the tourism suitability index (IKW). The results showed that the indeks of suitability of beach tourism on Pombo Island, at two observation stations, station 1 and station 2, that is